Efektifitas Modul IPAS Berbasis PBL terhadap Hasil Belajar Taruna Nautika Kapal Penangkap Ikan - Haerawati; Muhammad Fadli; Kartini J (Almeera Education, 2025)
The purpose of this study was to determine the effectiveness of the use of modules in the subject of problem-based science on learning outcomes. The method used in this study was a pre-experiment using a purposive sampling technique. The subjects of the study were 33 cadets of the Nautical Department of Fishing Vessels. The instruments used in this study were pretest and posttest questions. Data on the increase in students' pretest and posttest results had homogeneous variance and were normally distributed. Based on the paired t-test with a level of α = 0.05, Tcount (22.005)> Ttable (1.694) was obtained. This shows a significant increase in student learning outcomes. The results of the n-gain test based on the achievement of learning outcomes in students showed a value of 0.718 which was categorized as high. Therefore, the problem-based science module used is effective in improving learning outcomes.